Monetary Policy Signaling and Movements in the Swedish Term Structure of Interest Rates - Malin Andersson; Hans Dillén; Peter Sellin (Sveriges Riksbank, 2001)
This paper examines how various monetary policy signals such as repo rate changes, inflation reports, speeches, and minutes from monetary policy meetings affect the term structure of interest rates. We find that unexpected movements in the short end of the yield curve are mainly driven by unexpected changes in the repo rate, while speeches is a more important determinant for the longer interest rates. Hence, we conclude that central bank communication is an essential part of the conduct of monetary policy.
Keywords: E43; E44; E58; 330; Monetary policy signaling; central bank communication; the term structure of interest rates